To Activate the Brain, Activate the Body First - Habibzadeh, Nasim (International Physiology Journal, 2019)
The brain is the most complex organ which governs almost all activities in human body. Thus, the mental fitness has high level of importance in every day workouts. The good activities for long-term brain health include performing regular exercises such as a simple walking for 10 min at each day. More importantly having good level of diet can keep the brain workouts in an ideal situation. Indeed, taking enough rest can enhance the brain performances. Listening to the desirable sound of music could also enhance concentration and improve the mood. In overall, these aforementioned life style modifications significantly can easily boost the brain power and its healthy function through different aspects in daily life.
Keywords: Brain workout; Brain efficiency; Brain health